(untitled) (Research, Society and Development, 2022)
The functional performance and healthiness of the building are fundamental elements in civil construction, guaranteeing the absence of pathologies that interfere with its performance. Buildings must provide comfort and safety for the people who inhabit them. This study aimed to verify the technical, functional and maintenance compliances of the constructive components of a multifamily building, in the city of Garanhuns, Pernambuco, Brazil, seeking the diagnosis of pathological manifestations and their causes, according to the national building inspection standard. , by recommendations OP-003-2015 and by NBR 13752:92 (ABNT, 1996); NBR 6118 (ABNT, 2014); NBR 15775 (ABNT, 2013); NBR 7200 (ABNT, 19980); NBR 13281 (ABNT, 2005) and NBR 7584 (ABNT, 2012). In the methodology, bibliographic research, exploratory research and case study were used. The data obtained were subjected to investigation scope, credibility and information adjustments based on the technical quality of the analyses, the building inspection carried out was level 1. The study was prepared based on the basis of the analysis of risks associated with environmental use and exposure. The results found allowed the characterization of technical conformities and performance in service of the property, highlighting electrical and structural problems as the main problems to be repaired.